A Domain Ontology for Software Requirements Change Management in Global Software Development Environment - Abeer Abdulaziz Alsanad (IEEE Access, 2019)
Ontology and its role in both software engineering and knowledge management fields have been widely reported in the literature. Numerous studies have proven the effectiveness of using ontologies to support the process of requirements engineering. One of the main problems facing requirements engineering is that the requirements are exposed to change. In fact, this problem swells even more in global software development (GSD) environment. Given that this problem is unavoidable, we need to improve the requirements change management (RCM) process. In this paper, a systematic domain ontology for RCM especially in GSD environment is proposed. A hybrid method combining Methontology and the 101 method is used for its development; Web Ontology Language (OWL) for its representation; and Protégé for its implementation. It was validated using ontology content evaluation and competency question evaluation methods. Also, it was verified using both ontology taxonomy evaluation and FOCA evaluation methods. Validation and verification results showed that the proposed ontology was successfully built. Building this ontology can be considered as a base contribution in supporting the RCM process in GSD.